2017
DOI: 10.1038/srep38864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary Astragalus Polysaccharide supplements on testicular miRNA expression profiles and enzymatic changes of breeder cocks

Abstract: Astragalus Polysaccharide (APS) is an important feed additive due to its immunomodulatory functions. Previous studies have proven that miRNAs play important roles in posttranscriptional gene regulation. Our goals were to identify differentially expressed miRNAs in testes in responses to APS dietary supplements and to find the effects of APS on breeder cock testes. We measured several enzymatic activities in testes and sperm samples and further generated miRNA expression profiles of testes from breeder cocks fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…(h) 3 0 untranslated region luciferase reporter assays and PC-3p-448507_5 mimic or miR-NTC (RIBO Bio, Guangzhou, China) using 2.0 µl X-tremeGENE siRNA Transfection Reagent (Roche, USA) into HEK-293 T cells, the expression levels of PC-5p-30232_97 and PC-3p-448507_5 in cells were measured by quantitative real time-PCR (qRT-PCR) and then luciferase reporter experiments were performed [19].…”
Section: (F ) Rna Isolationmentioning
confidence: 99%
“…(h) 3 0 untranslated region luciferase reporter assays and PC-3p-448507_5 mimic or miR-NTC (RIBO Bio, Guangzhou, China) using 2.0 µl X-tremeGENE siRNA Transfection Reagent (Roche, USA) into HEK-293 T cells, the expression levels of PC-5p-30232_97 and PC-3p-448507_5 in cells were measured by quantitative real time-PCR (qRT-PCR) and then luciferase reporter experiments were performed [19].…”
Section: (F ) Rna Isolationmentioning
confidence: 99%
“…APS suppressed miR-721 expression to attenuate TNF-α-induced insulin resistance in 3T3-L1 adipocytes [30]. Dietary APS supplements could regulate testicular miRNA expression profiles [39]. But, none of these studies have explicitly demonstrated whether APS modulated miRNA expression by directly participating in the transcription, or indirectly by regulating miRNA sponges.…”
mentioning
confidence: 99%
“…33 the inhibitory effects of APS on porcine viruses infection have verified 34 and APS has been observed to regulate the levels of immunomodulating compounds in many different cell types. 35,36 The manifestation of adhesion molecules, including P-selectin and E-selectin, was inhibited by APS and persisted while the ECs were stimulated with CSFV, which could promote the expression of both P-and E-selectin ( Figure 2AB). Similarly, the increase of TF ( Figure 2D), TGF-β ( Figure 4C), and IL-8 ( Figure 3F) production in response to CSFV was inhibited by APS.…”
Section: Discussionmentioning
confidence: 99%